Compulsory Vaccination for Children in Malaysia: Issues and Challenges - Khairun-Nisaa, Asari; Nur Amani, Pauzai; Maheran, Makhtar; Farhanim, Abdullah Asuhaimi (2017)
The vaccination of children has proved to be one of the most effective and important health interventions in battling infectious diseases. Yet despite the phenomenal success of childhood vaccination, a growing number of parents in Malaysia choose not to vaccinate their children each year. These parents‘ decisions can be contributed to a growing rise of parental autonomy.